Experimental Investigation of Mechanical Properties of Al6061 Reinforced with Iron ore. (2017) - Marachakkanavar, Mailareppa; Sanjey, S.J.; Korade, D.N.; Jagtap, K.R.
Abstract: This work focuses on the fabrication of aluminum alloy (6061) matrix composites (AMCs) reinforced with 2 to 6 wt% iron ore of 150μm using stir casting route. The cast samples are heat treated by adopting T6 cycles, which includes solutionizing and ageing. The cast samples are solutionized at temperature 525°C for 6 hours followed by hot water quenching. The quenched samples are age hardened at 175°C for 8 hours followed by air cooling in open atmosphere. The ASTM standard test specimens are prepared from heat treated sample. The scanning electronics microscope and mechanical properties of the fabricated AMCs were analyzed. The mechanical properties like hardness and tensile strength of the unreinforced alloy and composites have been measured. The mechanical properties like hardness and tensile strength have improved with the increase in weight percentage of iron ore in the aluminum matrix.